Pemberian Pelatihan Pengambilan Darah Vena Dan Kapiler Pada Siswa SMK Negeri 17 Samarinda - Marsudi, La Ode; Aminuddin, Muhammad Fahmi; Susanto, Zaenal Adi; Putri, Maharani (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Blood collection, or phlebotomy, is the process of obtaining a blood sample from circulation through a puncture or incision. The medical personnel who perform this procedure are called phlebotomists. Typically, blood is drawn from the median cubital vein in the front of the arm (inside the elbow). If this vein is not accessible, the cephalic or basilic veins can be alternatives, and if these are also unsuitable, blood can be drawn from a vein in the wrist area. It is important to consider blood volume, especially in patients with anemia, newborns, or patients with small veins, to avoid insufficient blood collection. Adequate skills are required to obtain a qualified blood sample. The aim of this community service is to provide education and training to students on the proper methods for venous and capillary blood collection in accordance with standard procedures, and to minimize phlebotomy complications. The service methods include pre-tests, post-tests, material presentation, and phlebotomy practice. Out of 44 participants, after education, 88.6% understood phlebotomy, 86.3% understood ancient phlebotomy techniques, 100% understood modern techniques, 91% understood the types of veins and the first choice, 75% understood the order of venipuncture, 100% understood modern phlebotomy equipment, and 79.5% understood the use of tourniquets. In conclusion, participants' knowledge increased after phlebotomy training and education.